(untitled) - Fox, David (Corte Madera, CA, 1996)
HTML Web Publisher's Contruction Kit was one of the bestselling books in 1995. This new edition adds 150 pages of new material on the hottest new technologies on the Web--including Shockwave and other Netscape extensions, JavaScript, and Java. Information is presented in a hands-on lesson format, describing each tool in detail and explaining how all the parts are brought together to achieve the desired result.
Keywords: HTML (Document markup language),World Wide Web,Ngôn ngữ siêu văn bản,Mạng Internet